(untitled) (Teología, 2019)
This text is about the connection between the path of the Church of Latin America from Medellin and the Exhortation of John Paul II 31 years later, which extends the options of Medellin to all of America, North and South. We will make our reflection only on some highlights of this dense and important document, since it is impossible within the limits of this text, to cover everything. We will privilege some paragraphs and some aspects too. And this choice and selection will have to do with the context of Latin America, the south of this unique America that the Church desires united in a single vocation of fraternity.